Expressing Duration and Temporal Relationships by Means of the Present Perfect Progressive - Bégin, Claude (Revue québécoise de linguistique)

(untitled) (Université du Québec à Montréal, 2003)
AbstractThe Present Perfect Progressive often expresses an activity reaching up to the present, as in He has been speaking for two hours. Here the subject is represented after part of the event, hence the impression of an unfinished activity. In some cases, however, the completed portion of the event represents almost the whole event, as we shall see with explicit examples. In other cases still, the Present Perfect Progressive expresess a just- finished event, where the subject is situated after the whole event’s duration. The aim of this article is to answer the following question: how can the Present Perfect Progressive express different moments of the event’s duration and so evoke different types of events? As we shall see, the answer lies in the way that events are expressed by the present participle.